Chronic Monteggia in pediatric population: A narrative literature review - Chiara Arrigoni; Nunzio Catena (PAGEPress Publications, 2022)
Monteggia lesion is a traumatic condition that affects the forearm and is characterized by the association of an ulna fracture with a dislocation of the radius capitellar and proximal radius ulnar joints in the majority of cases. Although several authors have contributed to the understanding of this pathology over the years, it remains a challenge for orthopedists, and if not recognized and treated properly, it can have serious consequences. In these cases, a chronic injury develops, which is even more difficult to manage in terms of timing and treatment options. A narrative review of the literature on missed elbow injuries in children was conducted, and chronic Monteggia was the most frequently encountered injury. The analysis of the articles attempts to clarify some points and draw general conclusions on which to reflect.